IMPROVING STUDENTS’ READING COMPREHENSION THROUGH LISTEN READ DISCUSS (LRD) STRATEGY - Prayuda, Meikardo; Ginting, Fiber Yun Almanda; Sakerengan, Emilius (Pendidikan Bahasa Indonesia dan Sastra (PENDISTRA), 2023)
This research was conducted in order to find out wheter LRD Strategy can improve students’ Reading Comprehension in Recount Text and to know the students’ responses toward the learning reading comprehension through LRD Strategy. The subjects of this research were the tenth grade students at SMA Budi Murni 3 Medan. In conducting this research, the writer used Classroom Action Research (CAR) as the method of the research. The data collected used quantitative and qualitative data. Quantitative data was gained from the result of pre-test, formative test and post-test. Meanwhile, qualitative data was gained from the result of field notes, observation sheets and questionnaire toward students and teacher activity. The result showed that LRD Strategy can improve the students’ reading comprehension especially in recount text. The improvement can be seen from the student’s mean score in the pre-test is 52.41, in the formative test is 74.48, and in the post-test is 80. Furthermore, the students’ responses toward the method of the teaching learning process sound great because above 90% of the students are interested, motivated and understand the lesson with LRD Strategy.